Prostaglandin E2 Activates NLRP3 Inflammasome in Endothelial Cells to Promote Diabetic Retinopathy - Wang, Yixin; Tao, Jianxin; Yao, Yong (Hormone and Metabolic Research, 2018)
Proliferative diabetic retinopathy (PDR) is the leading cause of blindness and accounts for approximately 12% of all new cases of blindness. Prostaglandin E2 (PGE2) and nucleotide-binding domain and Leucine-rich repeat Receptor containing a Pyrin domain 3 (NLRP3) inﬂammasomes have been long considered to be associated with PDR. Levels of pro-inflammatory mediators were examined by Enzyme-linked immunosorbent assay (ELISA) measurements. PGE2 levels were analyzed by using the Prostaglandin E2 Monoclonal EIA Kit. Human retinal microvascular endothelial cells (HRMECs) were stained with Annexin V/propidium iodide and analyzed by ﬂow cytometry for testing the apoptosis. Expression levels of NLRP3 inflammasome components under various conditions were detected by Western blot and real-time PCR. Inﬂammasome markers and PGE2 were highly expressed in the vitreous of PDR patients. PGE2 and NLRP3 induced apoptosis of HRMECs. PGE2 upregulated the expression of NLRP3 inﬂammasome components and inﬂammatory chemokines. Knockdown of NLRP3 attenuated the expression of NLRP3 inﬂammasome components and inhibited the effect of PGE2. Our results suggest that PGE2 levels and NLRP3 inﬂammasome activation are closely related to the pathogenesis of PDR and nonsteroidal anti-inﬂammatory drugs may have a potential therapeutic effect on PDR.
Keywords: proliferative diabetic retinopathy (PDR); NLRP3 inﬂammasomes; prostaglandin E2 (PGE2); apoptosis